Degradasi Mekanik Beton Mutu Tinggi Pasca Bakar - Hamdi, Fauzan; Zainuddin, Muh Amir; Gaffar, Farida (Universitas Muhammadiyah Yogyakarta, 2018)
Research on the effect of temperature on concrete is still a hot topic. The effect of temperature was measured on its mechanical properties and analyzed using descriptive statistical analysis. The desire of researchers to know accurately the shape, description, and influence of temperature on concrete is something that still needs further research. The researchers began to research by making concrete test objects which were then burned directly in the furnace. After that, testing is done on the test object in the form of compressive strength. The research that was carried out was the remains of a burning building. But so far the assessment research has not yet found a strong starting point. Broadly speaking, the problem examined in this study is that researchers want to know the magnitude of high quality concrete mechanical degradation after being burned at a certain temperature and compared with high quality concrete that is not burned. These results are expected to provide a basis for the repetition of buildings that use high quality concrete that has been burned. The results of the mechanical degradation test reviewed were the average compressive strength of high quality concrete at a normal temperature of 53.46 MPa, a temperature of 100oC of 34.93 MPa, a temperature of 300oC of 29.76 MPa, a temperature of 600oC of 25.57 MPa.